ANALISIS DEIKSIS PERSONA DAN PERAN SEMANTIS DALAM KUMPULAN CERPEN KLOP KARYA PUTU WIJAYA - (F11409045), Revelino; Saman, Sisilya; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
This study aimed to describe the types, forms, functions, and semantic role deixsis persona contained in a collection of short stories